COMPARATIVE EFFECT OF LERCANIDIPINE, FELODIPINE, AND NIFEDIPINE GITS ON BLOOD PRESSURE AND HEART RATE IN PATIENTS WITH MILD TO MODERATE ARTERIAL HYPERTENSION: THE LERCANIDIPINE IN ADULTS (LEAD) STUDY - R. Romito; M. I. Pansini; F. Perticone; G. Antonelli; M. Pitzalis; P. Rizzon (Российский кардиологический журнал)
This multicenter, double-blind, parallel-group study compared the effects of three dihydropyridine calcium channel blockers (lercanidipine, felodipine, and nifedipine gastrointestinal therapeutic system, GITS) on blood pressure and heart rate in 250 patients with mild to moderate hypertension (diastolic blood pressure ≥95 mm Hg and ≤109 mm Hg). Patients were randomized to 4 weeks of treatment with once-daily doses of lercanidipine 10 mg, felodipine 10 mg, or nifedipine GITS 30 mg. After 4 weeks of treatment, the dose was doubled in nonresponding patients. At 8 weeks, no significant differences in blood pressure were observed among the three groups. Increases in heart rate in all three groups induced by stressful conditions before and after treatment were not exacerbated during active treatment. The incidence of adverse drug reactions was lower in the lercanidipine and nifedipine groups than in the felodipine group (р<0,05); in particular, the incidence of edema for lercanidipine was 5,5% vs. 13% for felodipine and 6,6% for nifedipine.